Fundamental challenges and complexities of damage identification from dynamic response in plate structures - Alshammari, Yousef Lafi A.; He, Feiyang; Alrwili, Abdullah Ayed; Khan, Muhammad (MDPI, 2024)
For many years, structural health monitoring (SHM) has held significant importance across diverse engineering sectors. The main aim of SHM is to assess the health status and understand distinct features of structures by analyzing real-time data from physical measurements. The dynamic response (DR) is a significant tool in SHM studies. This response is used primarily to detect variations or damage by examining the vibration signals of DR. Numerous scholarly articles and reviews have discussed the phenomenon and importance of using DR to predict damages in uniform thickness (UT) plate structures. However, previous reviews have predominantly focused on the UT plates, neglecting the equally important varying thickness (VT) plate structures. Given the significance of VT plates, especially for academic researchers, it is essential to compile a comprehensive review that covers the vibration of both the UT and VT cracked plate structures and their identification methods, with a special emphasis on VT plates. VT plates are particularly significant due to their application in critical components of various applications where optimizing the weight, aerodynamics, and dimensions is crucial to meet specific design specifications. Furthermore, this review critically evaluates the damage identification methods, focusing on their accuracy and applicability in real-world applications. This review revealed that current research studies are inadequate in describing crack path identification; they have primarily focused on predicting the quantification of cracks in terms of size or possible location. Identifying the crack path is crucial to avoid catastrophic failures, especially in scenarios where the crack may propagate in critical dimensions of the plate. Therefore, it can be concluded that an accurate analytical and empirical study of crack path and damage identification in these plates would be a novel and significant contribution to the academic field.
Keywords: 4005 Civil Engineering; 3403 Macromolecular and Materials Chemistry; 40 Engineering; 34 Chemical Sciences; vibration measurements; dynamic response; cracked plate; intact plate; damage detection; uniform thickness; varying thickness